Strategi Komunikasi Internal Pimpinan PT Haleyora Powerindo Jatinegara Dalam Meningkatkan Kinerja Karyawan Studi Kasus Pada Bidang Management Billing. - Dzahra Humairah Fikriya; Robbikal Muntaha Meliala; Teguh Tri Susanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the internal communication strategy of leaders in improving employee performance at PT Haleyora Powerindo Jatinegara, with a case study on officers in the Management Billing field. The research problem stems from the ineffectiveness of the implementation of internal communication which has an impact on employee performance, indicated by low discipline, suboptimal delivery of information, and lack of employee understanding of their duties and responsibilities. This study uses a qualitative descriptive method with data collection techniques through in-depth interviews, participant observation, documentation, and literature studies. The results of the study show that the internal communication strategy implemented by leaders is carried out through morning briefings (COC), two-way communication through WhatsApp groups, motivational delivery, and strengthening vertical, horizontal, and diagonal communication. In addition, employee relations activities such as family gatherings held every two years and the Best Employee award given routinely at the end of each year, also play a role in improving work relations, motivation, and employee performance. The implementation of this internal communication strategy has an impact on increasing employee understanding, discipline, and responsibility in carrying out tasks. However, efforts are still needed to improve in terms of consistency of discipline and effectiveness of communication so that organizational goals can be achieved optimally.